2012
DOI: 10.21608/jpp.2012.84182
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Different Rice Genotypes Under Application of Phosphorus Fertilizer Levels

Abstract: Phosphorus is one of the essential macronutrient element not only for rice but also for other plants, it is important for plant metabolism and enzymatic activity during the periods of growth and grain filling. Rice growth, yield and its attributes strongly influenced by phosphorus nutrition. This investigation was conducted to study the performance of different rice genotypes i.e. Sakha105 and Sakha106 (japonica), Giza178 (indica/japonica) and Giza182 (indica) under four phosphorus levels namely 0, 18, 36 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 10 publications
7
3
0
Order By: Relevance
“…Application of P fertilizer resulted in ensuring high ATP, which provided high photosynthesis resulted in more assimilates in pre and post heading, which lead to improve panicle filling and consequently increase in weight of panicle. These data are in agreement with those obtained by Sahar and Burbey (2003), Metwally et al, (2012) and Naeem et al, (2016).…”
Section: Yield Attributessupporting
confidence: 93%
See 4 more Smart Citations
“…Application of P fertilizer resulted in ensuring high ATP, which provided high photosynthesis resulted in more assimilates in pre and post heading, which lead to improve panicle filling and consequently increase in weight of panicle. These data are in agreement with those obtained by Sahar and Burbey (2003), Metwally et al, (2012) and Naeem et al, (2016).…”
Section: Yield Attributessupporting
confidence: 93%
“…The data also showed that, in both seasons, the untreated control plants (P1) gave the shortest panicle. These results are in agreement with those of Sahar and Burbey (2003), and Metwally et al (2012). Application of foliar spray treatments and their interaction did not show any significant variation in respect of panicle length in both seasons.…”
Section: Yield Attributessupporting
confidence: 92%
See 3 more Smart Citations